PENGARUH WORK LIFE BALANCE, KOMPETENSI, DAN KOMITMEN TERHADAP KINERJA PEGAWAI DI PUSKESMAS PERAWATAN TES KABUPATEN LEBONG - Ayudia Asti Adevio; Ratnawili Ratnawili (UM. Bengkulu, 2026)
This study aims to analyze the influence of work life balance, competence, and commitment on employee performance at the Lebong Regency Test Care Health Center. The research has been carried out since December 2024 using quantitative methods and saturated sampling techniques, so that all employees totaling 50 people are used as samples. Data collection was carried out through a closed questionnaire with a Likert scale, documentation, and observation. The validity and reliability test of the instrument was carried out on 20 employees of the Talang Leak Health Center, while the data analysis used multiple linear regression assisted by SPSS 26. The results showed that partially, work life balance (t count = 3.197; sig. = 0.003), competence (t count = 11.178; sig. = 0.000), and commitment (t count = 6.338; sig. = 0.000) had a positive and significant effect on employee performance. Simultaneously, these three variables also had a significant effect on performance (F count = 169.998; sig. = 0.000). The determination coefficient value (R²) of 0.917 indicates that 91.7% of the variation in employee performance can be explained by work life balance, competence, and commitment, while the rest is influenced by other factors outside the study. These findings affirm the importance of strengthening competencies, improving work-life balance, and employee commitment to support optimal performance in the Puskesmas. Keywords: Work Life Balance, Competence, Commitment and Performance